Miniaturized turbidimetric assay: A green option for the analysis of besifloxacin in ophthalmic suspension - Tótoli, Eliane Gandolpho [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Elsevier, 2020)
Besifloxacin is an important antimicrobial agent, belonging to the class of fluoroquinolones, used in the treatment of infectious conjunctivitis. Quality control of this active pharmaceutical ingredient is essential, since poor quality antimicrobials may contribute to the aggravation of the worrying picture of bacterial resistance. Thus, analytical methods need to be developed, validated and improved for that purpose. It is also important that these methods be environmentally friendly, as ensuring the quality of products without harming the environment meets the global needs. The aim of the study was the development and validation of a miniaturized turbidimetric microbiological method for the analysis of besifloxacin hydrochloride (BSF) in ophthalmic suspension. The analyzes were performed in 96-well microplates using Staphylococcus epidermidis ATCC 12228 as test microorganism and BHI broth. The method was validated according to ICH guidelines and showed to be linear (in a range of 0.5–8.0 μg mL−1), precise, accurate, robust and selective. Study of photo-degradation kinetics of BSF sample showed a zero order reaction. A comparative study with a previously validated HPLC method showed that the methods are interchangeable. This work shows the great potential of the proposed method of being introduced in routine analyzes of quality control of BSF in ophthalmic suspension as an option in line with the principles of Green Chemistry.
Keywords: Besifloxacin; Green chemistry; Miniaturized turbidimetric assay; Quality control; Validation